Introduction to Charles Honorton’s 1993 Firsthand Report on Felicia Parise and Rosemarie Pilkington’s 2013 Interview with Felicia Parise - Braude, Stephen (Journal of Scientific Exploration, 2015)
Readers of the JSE will have recently been exposed to some data and issues regarding macro-PK (see, in particular, Volume 28, Number 2). And probably many JSE readers realize that some individuals seem to have demonstrated the ability to psychically influence, and in particular move, ordinary visible objects outside of the spiritist context characteristic of physical mediumship-that is, by means of one's own ostensible PK abilities and without invoking the assistance of deceased spirits to produce the effects. The Russian Nina Kulagina may be the best-known twentieth-century example. However, another interesting mid-twentieth-century case, roughly contiguous with that of Kulagina, is the case of the American Felicia Parise. However, very little has been written about this case. I'm pleased, then, that we're able to present in this issue Rosemarie Pilkington's very recent interview with Felicia in 2013, which brings the case up to date and contributes substantially to what little is known about it. Moreover, for readers who've never heard about Felicia-and to refresh the memories of others-we're pleased to reprint the late Charles Honorton's 1993 report of his firsthand experiences with Felicia.